Manajemen Sumber Daya Manusia Dalam Lembaga Pendidikan - Fika, Nurul; Zohriah, Anis (Jambura Journal of Educational Management, 2024)
Human resources (HR) is one of the most important factors that cannot even be separated from an organization, both institutions and companies. In essence, human resources are people who are employed in the organization as movers, thinkers and planners to achieve organizational goals. Therefore, human resources are very important and need to be managed effectively. As forthis research, it aims to describe human resource management in Islamic educational institutions. This research uses a type of descriptive qualitative research, with a literature review approach. This study examines the understanding of human resources, the terms educators and educational personnel, the purpose of educational human resource management, and the substance and function of education human resource management